Weaving a national map : review of the U.S. Geological Survey concept of the national map - Cowen, David J. (National Academies Press, 2003)
This report responds to a request by the U.S. Geological Survey (USGS) that the National Research Council (NRC) review its concept of The National Map. The National Map is envisioned by USGS as a database providing "public domain core geographic data about the United States and its territories that other agencies can extend, enhance, and reference as they concentrate on maintaining other data that are unique to their needs" (USGS, 2001). A motivation behind The National Map is the need to update aging national paper map coverage.